Civilizing the Public Sphere - Papakostas, Apostolis. author. aut Link
XV, 190 p.
Keywords: Examining the interplay between distrust, trust and corruption, this book maps out the social mechanisms that make actors and organizations in the public sphere perform their activities in a civilized manner.